2016
DOI: 10.1038/srep23636
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Effects of Lung function test on Postoperative Pneumonia in Squamous Esophageal Cancer

Abstract: Pulmonary function tests had prospective implications for postoperative pneumonia, which occurred frequently after esophagectomy. Understanding factors that were associated with pulmonary infection may help in patient selection and postoperative management. We performed a retrospective review of 2 independent cohorts including 216 patients who underwent esophagectomy between November 2011 and May 2014, aiming at identifying predictors of primary pneumonia. Univariate analysis was used to identify potential cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Similarly, lung function tests may also play a role. A retrospective review by Wei et al [ 21 ] assessed 216 esophagectomy patients, and found a postoperative pneumonia incidence rate of 10.24%. Preoperative oral care may help prevent postoperative pneumonia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, lung function tests may also play a role. A retrospective review by Wei et al [ 21 ] assessed 216 esophagectomy patients, and found a postoperative pneumonia incidence rate of 10.24%. Preoperative oral care may help prevent postoperative pneumonia.…”
Section: Resultsmentioning
confidence: 99%
“…Okamura et al [ 20 ] identified higher lung age (OR: 1.02; 95% CI: 1.00 - 1.03; P = 0.010) and lower body mass index (OR: 0.89; 95% CI: 0.82 - 0.96; P = 0.006) as independent risk factors. Wei et al [ 21 ] found that low peak expiratory flow was an independent risk factor for postoperative pneumonia (HR: 0.97; 95% CI: 0.94 - 0.99; P = 0.009). Several independent risk factors identified by Soutome et al [ 22 ] included: diabetes mellitus (OR: 2.961; 95% CI: 1.159 - 7.565; P = 0.023), postoperative dysphagia (OR: 8.879; 95% CI: 4.295 - 18.352; P ≤ 0.001), and absence of preoperative oral care (OR: 0.422; 95% CI, 0.209 - 0.851; P = 0.016).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have identified numerous patient-related or procedure-related risk factors for POP after femoral neck fracture surgery. In most but not all studies, multiple variables, including older age, male sex, and the presence of several key clinical comorbidities such as chronic obstructive pulmonary disease (COPD), 5 obesity, 7,8 tobacco smoking, 9 prior stroke, 3 impaired preoperative pulmonary function, 10,11 cognitive and functional premorbid status 12 and cardiovascular disease 3 have been identified as risk factors for POP.…”
Section: Introductionmentioning
confidence: 99%
“…22 Preoperative pulmonary function (reflected in the forced expiratory volume in 1 second expressed as a percentage of the forced vital capacity and peak expiratory flow) is also associated with major complications after esophagectomy. 23,24 Pulmonary complications can be reduced by minimally invasive surgery, thoracic epidural analgesia, and early enteral nutrition. 25 Other strategies to improve preoperative condition of the patient include physical therapy to increase cardiorespiratory function.…”
Section: Patient Selection For Surgerymentioning
confidence: 99%